Representasi Klaim Merakyat dalam Iklan TVC “Coblos Nomor 3, Menangkan Rakyat” Pasangan Ganjar-Ma’fud dalam Iklan Pemilihan Presiden 2024 - Muhammad Furqon Dwi Nur Rohmad; Fajar Junaedi (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the representation of the populist claim in the political advertisement of the Ganjar-Ma’fud duo, titled "Vote for Number 3, Champion the People," during the 2024 Presidential Election. Using Roland Barthes' semiotics approach, this research explores the meanings embedded in the advertisement, focusing on three main aspects: denotation, connotation, and myth. The analysis covers 3 scenes in the advertisement, highlighting the role of celebrities as symbols of the people. The findings reveal that the advertisement strategically employs celebrities to create an image of the candidates as close to the public. At the denotative level, celebrities are shown in situations depicting togetherness with the general public. The connotation that arises is that these celebrities represent the entire populace, giving the impression that the Ganjar-Ma’fud pair genuinely represents the people's interests. The myth created reinforces the narrative that celebrities, due to their popularity, possess the capability to represent and advocate for the people's aspirations in the political arena. This study underscores the significance of television as an effective political campaign tool, despite the growing dominance of social media. The findings provide insights into political communication strategies that leverage celebrity popularity to garner public attention and support. The study suggests further exploration into the long-term impact of using celebrities in political campaigns on public trust and the quality of democracy.